From Isolation to Connection: The Practices and Promise of Open Domestic Violence Shelters - Goodman, Lisa A. (Journal of interpersonal violence, 2022)
Antidomestic violence advocates have begun to question two essential policies that have long defined domestic violence shelters?strict secrecy regarding shelter location and prohibitions on shelter access to all except staff and residents?both of which serve to increase survivors? social isolation and entail coercive rules that resonate painfully with broader oppressive dynamics. In response a growing number of communities have begun experimenting with open shelters, which break from tradition by making their locations public, and allowing visitors. Although this innovation is a sharp departure from tradition, virtually no research exists to explore its philosophical underpinnings, benefits, and challenges. This study addresses this gap. Study Questions: We used a qualitative descriptive approach to explore the experiences and perspectives of open shelter directors. Participants included 14 open shelter directors from 11 states. We conducted semistructured phone interviews with each participant, focusing on their shelter?s (a) nature and history; (b) rationale; (c) policies and programs related to secrecy and openness; (d) benefits and challenges; (e) effects on specific survivor subgroups; and (f) practices used to build or strengthen survivors? relationships. Open shelters: (a) promote physical safety using a broad array of measures; (b) adopt a range of policies that promote varying degrees of location disclosure and visitor accessibility; (c) face challenges, such as the need to gain buy-in from multiple constituents; and (d) Improve survivor outcomes, including decreased shame; improved advocacy relationships; increased access to services and community involvement in shelter life; and deepened relationships with network members; in turn increasing prospects for physical and psychological well-being long after survivors? shelter stays are over. Findings suggest a new path for shelters interested in promoting survivor safety and healing in the context of a web of meaningful relationships.